Analysis of Community Composition of Bacterioplankton in Changle Seawater in China by Illumina Sequencing Combined with Bacteria Culture. Issue 1 (24th November 2021) - Wang, Du; Zheng, Qingcong; Lv, Qi; Cai, Yuanqing; Zheng, Yun; Chen, Huidong; Zhang, Wenming
Abstract : Objectives: To characterize the abundance and relative composition of seawater bacterioplankton communities in Changle city using Illumina MiSeq sequencing and bacterial culture techniques. Methods: Seawater samples and physicochemical factors were collected from the coastal zone of Changle city on 8 September 2019. Nineteen filter membranes were obtained after using a suction filtration system. We randomly selected eight samples for total seawater bacteria (SWDNA group) sequencing and three samples for active seawater bacteria (SWRNA group) sequencing by Illumina MiSeq. The remaining eight samples were used for bacterial culture and identification. Alpha diversity including species coverage (Coverage), species diversity (Shannon–Wiener and Simpson index), richness estimators (Chao1), and abundance‐based richness estimation (ACE) were calculated to assess biodiversity of seawater bacterioplankton. Beta diversity was used to evaluate the differences between samples. The species abundance differences were determined using the Wilcoxon rank‐sum test. Statistical analyses were performed in R environment. Results: The Alpha diversity in the SWDNA group in each index was ACE 3206.99, Chao1 2615.12, Shannon 4.64, Simpson 0.05, and coverage 0.97; the corresponding index was ACE 1199.55, Chao1 934.75, Shannon 3.49, Simpson 0.09, and coverage 0.99. The sequencing results of seawater bacterial genes in the coastal waters of Changle city showed that the phyla of high‐abundance bacteria of both the SWDNA and SWRNA groups included Cyanobacteria, Proteobacteria, and Bacteroidetes . The main classes included Oxyphotobacteria, Alphaproteobacteria, and Gammaproteobacteria . The main genera included Synechococcus CC9902, Chloroplast, and Cyanobium_PCC‐6307 . Beta diversity analysis showed a significant difference between the SWDNA and SWRNA groups ( P  < 0.05). The species abundance differences between SWDNA and SWRNA groups after Wilcoxon rank‐sum test showed that, at the phylum level, Actinomycetes was more abundant in SWDNA group (9.17 vs 1.02%, P  < 0.05); at the class level, Actinomycetes ( δ‐ Proteus ) was more abundant in SWDNA group (9.47% vs 1.01%, P  < 0.05); and at the genus level, Chloroplast was more abundant in SWRNA group (13.07% vs 44.57%, P  < 0.05). Nine species and 53 colonies were found by bacterial culture: 20 strains of Vibrio (37.74%), 22 strains of Enterobacter (41.51%), and 11 strains of non‐fermentative bacteria (20.75%). Conclusion: Illumi MiSeq sequencing of seawater bacteria revealed that the total bacterial community groups and the active bacterial community groups mainly comprised Cyanobacteria, Proteobacteria, and Bacteroides at the phylum level; Oxyphotobacteria, α‐Proteobacteria, and γ‐Proteobacteria at the class level; with Synechococcus_CC9902, Chloroplast, and Cyanobium_PCC‐6307 comprising the predominant genera. Exploring the composition and differences of seawater bacteria assists understanding regarding the biodiversity and the infections related to seawater bacteria along the coast of the Changle, provides information that will aid in the diagnosis and treatment of such infections. Abstract : In the SWDNA and SWRNA groups, the dominance of the phyla were Cyanobacteria, Proteobacteria, and Bacteroides ; the main classes were oxygen‐producing photobacteria, α‐proteobacteria, and γ‐proteobacteria . The predominant genera are Synechococcus_CC9902, Chloroplast, Cyanobium_PCC‐6307, Candidatus Actinomarina, Ascidiaceihabitans and HIMB11 in SWDNA; Chloroplast, Synechococcus_CC9902, HIMB11, Cyanobium_PCC‐6307, Ascidiaceihabitans, and Ralstonia in SWRNA.